Gêneros do discurso no jornalismo em quadrinhos brasileiro - Menezes, Luiz Fernando Nascimento [UNIFESP] (2019)
Since the publication of Joe Sacco's Palestine in the 1990s, Comics Journalism (CJ), name given to productions that link the journalistic discourse to the language of comics, have become popular. Works that used the CJ label became more frequent, including in Brazil. CJ, however, was born well before Sacco's work: at the end of the 19th century, italian-brazilian Angelo Agostini worked both as a journalist and as a comic artist, producing graphic reports about a wide range of subjects. Despite not being recent and having become popular about 30 years ago, CJ is still a matter of divergences when it comes to defining exactly what it is. Is it a Journalism genre or a Comics genre? This research takes as a starting point the assumption that Journalism and Comics are distinct discursive spheres, each with different traditions, organizations and languages, and the hypothesis already discussed by Souza Júnior (2010), Archer (2010) and Ramos (2016) that there are different journalistic genres within the CJ label: there are, for example, comic interviews, comic short-biographies and comic news. By analyzing three Brazilian works — Cortabundas (RODRIGUES, 2015), Notas de um tempo silenciado (VILALBA, 2015) and Raul (DE MAIO, 2018) —, we intend to verify the generic differences of the journalistic discourse. For the analysis, we will mainly use the theoretical perspective of discourse genres elaborated by Bakhtin (2016 [1952-1953], 2016 [1950], 2016 [1952]) and your Circle and the discussion about journalistic genres here in Brazil conducted by Marques of Melo (2010, 2016) and Seixas (2009). Lage (2017b [2005]) and Traquina (2005a, 2005b) will also be used to define the characteristics of the journalistic discourse, as well as specific authors for each of the three journalistic genres found in the works. In the Comics studies, it will be used, specially, Cagnin (2014), for the languages characteristics, and Duncan, Taylor and Stoddard (2016), for the history of Comics and Journalism relationship. Thanks to the dialogical perspective adopted and the chosen works, it was possible to verify the existence of different genres and, therefore, that JHQ is just a label given to journalistic productions finished with the comics language.